Feasibility and preliminary effects of an app-based physical activity intervention for individuals with depression (MoodMover): A protocol for a single-arm, pre-post intervention study - Yiling Tang; Madelaine Gierc; Henry La; Sam Liu; Raymond W. Lam; Eli Puterman; Guy Faulkner (PLoS ONE, 2025)
Depression is the leading cause of disability worldwide. Mobile app-based behavior change interventions that promote lifestyle physical activity (PA) may serve as viable alternatives or adjuncts to traditional treatments offering increased reach and accessibility. This protocol describes an experimental, pre-post single-arm trial to investigate the feasibility and preliminary effects of an app-based, 9-week PA intervention (MoodMover) designed for individuals with depression. MoodMover is co-designed with patients and a multidisciplinary research team using a no-code intervention development platform (Pathverse). This study will employ a single-arm pre-post trial with an optional 9-week follow-up, following the Obesity-Related Behavioral Intervention Trials (ORBIT) model. Thirty-six adults who self-report a clinical diagnosis of major depressive disorder or report at least mild depressive symptoms based on the Patient Health Questionnaire – 9 items (PHQ-9) will be recruited. The main outcomes of this study are the feasibility and acceptability of MoodMover, such as the recruitment strategy, assessments (e.g., PHQ-9), and user engagement. Preliminary effects will be assessed by evaluating changes in PA and depressive symptoms. Recruitment is expected to begin on November 1st, 2024, and end on May 1st, 2025. Trial results will be disseminated via publications in peer-reviewed journals and via presentations at academic conferences. This study fits within Phase IIa: Proof-of-concept and Phase IIb: Pilot and Preliminary Testing of the ORBIT model. The robust feasibility and acceptability measures, especially the user engagement data powered by Pathverse, will provide a comprehensive understanding of the MoodMover intervention’s feasibility and potential effects. Results will inform potential progression to the next step of the ORBIT model—Phase IIc: Phase II Efficacy Trial—to test MoodMover in a more rigorous randomized controlled trial. This study has been registered at ClinicalTrials.gov (NCT06573125; https://clinicaltrials.gov/study/NCT06573125).